Comment on “The diatomic dication CuZn2+ in the gas phase” [J. Chem. Phys. 135, 034306 (2011)] - Pis Diez, Reinaldo (2013)
In this Comment, the density functional theory (DFT) calculations carried out by Diez et al. [J. Chem. Phys. 135, 034306 (2011)10.1063/1.3613624] are revised within the framework of the coupled-cluster single double triple method. These more sophisticated calculations allow us to show that the 2Σ+ electronic ground state of CuZn2+, characterized as the metastable ground state by DFT calculations, is a repulsive state instead. The 2Δ and 2Π metastable states of CuZn2+, on the other hand, should be responsible for the formation mechanism of the dication through the near-resonant electron transfer CuZn+ + Ar+ → CuZn2+ + Ar reaction.